INFLUENCE OFDIFFERENTCONCENTRATION OF CURCUMIN (DIFERUOYL METHANE) ON FROZEN SEMEN QUALITY OF HOLSTEIN BULLS BORN IN IRAQ - Saleem, Abdul-Redha Hussein; Badry, Kareem Iwaid Al-; Ibrahim, FarisFaisel; J.Y, Khitam (International Journal of Psychosocial Rehabilitation, 2020)
Object :The current study was designed to improve semen preserve ability through the use of curcumin (diferuoyl methane) in different concentrations T1 0.5 ,T2 1.0 , T3 1.5 mM/ml and control (without additive) as extender additive expressed in frozen bull semen .Methods: Ejaculates less than 40% of initial individual motility were taken weekly from (3) Holstein bulls born in Iraq by using the artificial vagina. The semen samples were diluted with Tris containing different concentrations of curcumin (0.5, 1.0, 1.5)mM/ml and control (without additive), cooled slowly up to 5 Cº and equilibrated for 4hrs, semen was packed into 0.25 ml of straws and freezing and storage 48hrs in liquid nitrogen. Evaluated of semen for individual motility%, dead% ,abnormality%, acrosome integrity% and HOST%.at steps of freezing (after cooling and Post thawing).Results: Clearly indicated that, addition 1.5 mM of curcumin to tris diluents had significantly (P